Problem-Based Learning Materials Integrated with Differentiated Approaches to Enhance Elementary School Students' Learning Outcomes - Agusdianita, Neza; Danim, Sudarwan; Susanta, Agus; Yusnia, Y.; Izzania, Rizqa Dwi Shofiya Maghfira; Irmayanti, Meiselina (Universitas Muhammadiyah Surakarta, 2024)
The demands of the 21st century have reshaped the educational landscape, particularly in mathematics, requiring students to acquire relevant competencies. However, many elementary students find abstract mathematical concepts challenging, highlighting the need for effective instructional materials. This study employed a Research and Development (R&D) approach using the ADDIE model. Data were collected through questionnaires and multiple-choice tests, and the analysis was conducted using descriptive statistics and inferential analysis. Instructional materials integrating Problem-Based Learning (PBL) with a differentiated approach were designed and evaluated for validity, practicality, and effectiveness in teaching the perimeter and area of squares and rectangles to fifth-grade elementary students. Teacher and student feedback indicated that the materials were highly practical, and no significant obstacles were encountered. The analysis of student learning outcomes showed a significant improvement in mathematics achievement. These results imply that differentiated PBL materials can enhance students' learning experiences and outcomes, providing a viable solution for addressing individual learning needs in mathematics education. By providing relevant and tailored materials, educators can more effectively address abstract learning challenges and meet the demands of 21st-century competencies.